Self-supporting multifunctional catalytic fabric electrode and preparation and application thereof
Through the preparation of self-supported fabric electrodes of graphite felt/cobalt@nitrogen doped carbon nanotube array, the problems of high catalytic activity and multifunctional application are solved, and the efficiency and flexibility of flexible energy storage and sensing systems are achieved. In smart wearable devices and electrolytic aquatic hydrogen systems.
Patent Information
- Application Number
- CN202411234258.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-04
- Publication Date
- 2025-01-10
AI Technical Summary
The prior art is difficult to achieve multifunctional and multi-application self-support electrodes while maintaining high catalytic activity, especially in flexible energy storage and sensing systems, and traditional energy storage devices cannot meet the flexibility of smart wearable devices and Efficiency requirements.
采用石墨毡/钴@氮掺杂碳纳米管阵列自支撑织物电极的制备方法,通过室温自组装法和气相沉积法,原位生长金属有机框架和碳纳米管,形成高氮掺杂和富氧缺陷的碳纳米管封装Co颗粒,作为柔性自支撑双功能催化电极。
Achieve high catalytic activity and mechanical stability, able to act as flexible energy storage devices and sensing system components for wearable devices and electrolytic aquatic hydrogen systems, exhibiting excellent cycling stability and output power, and at different compression ratios Monitor human activities.
Smart Images

Figure CN119287421A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of air electrode materials, and in particular relates to a self-supporting multifunctional catalytic fabric electrode and preparation and application thereof. Background Art
[0002] The continuous consumption of fossil fuels has promoted the development of energy storage and conversion devices. Multifunctional electrocatalysts have great capabilities in energy storage and conversion systems to alleviate today's energy crisis. However, due to the complexity of material synthesis and electrode construction, it remains a challenge to achieve multifunctional and multifunctional applicability while maintaining high catalytic activity.
[0003] A possible alternative to solve the environmental problems caused by the excessive use of fossil fuels is hydrogen, which is ecologically acceptable, high in density, and can be considered as a green energy source. It can be produced through the process of water electrolysis via the hydrogen evolution reaction (HER). In energy conversion systems, water splitting via electrocatalysis produces H 2 It is a popular and effective approach. Improving the corresponding catalytic stability is the main direction to improve the efficiency of electrocatalytic water splitting.
[0004] Nowadays, smart wearable devices are becoming an emerging technology that can change human health and lifestyle. Sensors are inseparable from energy storage devices. In this regard, traditional energy storage devices can no longer meet consumers' demand for smart wearable devices with diverse functions. Although lithium-ion batteries (LIBs) are the most commercially successful electrochemical energy storage devices, the inflexibility and bulkiness of these rigid energy storage devices pose challenges to the operation of flexible sensing systems. Therefore, as a crucial component of sensing devices, flexible energy storage devices with high specific energy, long-lasting power supply, excellent flexibility and inherent safety are urgently needed. Self-powered sensing systems that integrate flexible energy storage components with flexible sensing components are of great significance to the development of wearable flexible devices.
[0005] In view of the portability and flexibility of wearable electronic devices, the materials of flexible batteries also need to have sufficient flexibility, so the development of self-supporting flexible electrodes is crucial for the practical application of rechargeable batteries. Commonly used self-supporting electrode materials include metal foams (Ni, Cu) and carbon materials, among which polyacrylonitrile graphite felt in carbon material fabric electrodes has the advantages of certain thickness, light weight, good flexibility, high carbon content, high temperature resistance, non-volatility at high temperature, corrosion resistance, low thermal conductivity, and high conformality. And because of the excellent adsorption capacity of graphite felt, metal particles can be evenly and firmly adsorbed on the fiber by a simple method, and a self-supporting electrode is obtained by in-situ growth. Therefore, the present invention is based on constructing a self-supporting multifunctional catalyst electrode of a transition metal-based material co-modified nitrogen-carbon (MN / C type) nanotube array on graphite felt, which can meet the requirements of achieving multifunctional and multifunctional applicability while maintaining high catalytic activity. Summary of the invention
[0006] In order to overcome the above-mentioned shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a method for preparing a self-supporting multifunctional catalytic fabric electrode.
[0007] Another object of the present invention is to provide a self-supporting multifunctional catalytic fabric electrode prepared by the above method.
[0008] Another object of the present invention is to provide the application of the above-mentioned self-supporting multifunctional catalytic fabric electrode. On the one hand, the present invention uses such electrodes to assemble flexible batteries as flexible energy storage devices to overcome the inflexibility of rigid energy storage devices and provide energy; on the other hand, such electrodes are used as cathodes and anodes of a self-driven water electrolysis hydrogen production system to decompose and produce hydrogen, and the energy supply device is a flexible energy storage device assembled by itself; finally, the electrode is used as a wearable-battery integrated device to monitor human physiological health activities, play a role in medical health, sports monitoring, entertainment and communication, and promote the rapid development of true sensing-energy supply-integrated wearable electronic systems. This invention promotes its multifunctional and multifunctional applicability while maintaining high catalytic activity.
[0009] The purpose of the present invention is achieved through the following solutions:
[0010] A method for preparing a graphite felt / cobalt@nitrogen-doped carbon nanotube array self-supporting fabric electrode comprises the following steps:
[0011] (1) Preparation of GF / Co fabric electrode by room temperature self-assembly method: Soluble cobalt salt and polyvinyl pyrrolidone are added to methanol, marked as liquid A, which is pink, and graphite felt is immersed in liquid A; dimethyl imidazole is added to methanol, marked as liquid B, which is colorless; after immersion in liquid A, liquid B is poured into liquid A and stirred until it turns purple, and then it is immersed and allowed to stand for self-assembly, and the graphite felt is taken out, cleaned, and dried to obtain a GF / Co fabric electrode;
[0012] (2) Preparation of GF / Co@NCNTs fabric electrode by vapor deposition: The fabric electrode obtained in step (1) above was placed flat on a porcelain boat containing a nitrogen-containing organic compound, keeping the fabric electrode covering the nitrogen-containing organic compound, and placing the porcelain boat in the center of a tube furnace. 2 Or high-temperature carbonization is carried out under an inert atmosphere. After the reaction is completed, it is naturally cooled to room temperature, and the sample is taken out to obtain a GF / Co@NCNTs self-supporting fabric electrode.
[0013] The graphite felt described in step (1) is preferably pretreated before the step (1) is performed. The pretreatment specifically comprises the following steps: the graphite felt is ultrasonically cleaned in acetone to remove organic residues on the surface of the graphite felt, then the acetone is poured out, anhydrous ethanol is added to ultrasonically clean the graphite felt to remove the residual acetone, the graphite felt is dried, and then the graphite felt is placed in an acidic solution and stirred for reaction, and finally the graphite felt is taken out and repeatedly washed with water and ethanol until it is neutral, and then dried for use in step (1).
[0014] The acidic solution in the pretreatment is preferably a mixed aqueous solution of sulfuric acid and nitric acid, which is obtained by mixing 98% concentrated sulfuric acid (concentration of 18.4 mol / L), 98% concentrated nitric acid (concentration of 15.56 mol / L) and water in a volume ratio of 1:0.5-2:0.5-2. The reaction temperature in the pretreatment is 60°C to 100°C, preferably 70°C, and the reaction time is 12 to 36h, preferably 24h. Put it in the acidic solution and stir the reaction to hydrophilize the graphite felt, and secondly make the surface of its carbon fiber rougher so that the surface area is increased and the particle adsorption is more sufficient. The drying temperature in the pretreatment is 50-60°C.
[0015] The soluble cobalt salt described in step (1) includes but is not limited to at least one of nitrate, sulfate, acetate, etc., wherein the soluble cobalt salt is preferably cobalt nitrate hexahydrate.
[0016] The molar ratio of the soluble cobalt salt, polyvinyl pyrrolidone and 2-methylimidazole in step (1) is 1:0.001-0.006:5-20, preferably 1:0.003:10.
[0017] The methanol added in step (1) satisfies the following conditions: the concentration of soluble cobalt salt in solution A after complete dissolution is 0.01-0.05 mol / L, and the concentration of 2-methylimidazole in solution B is 0.2-0.6 mol / L. 2 Add the corresponding amount of graphite felt into 2-10mL of liquid A.
[0018] The soaking in liquid A in step (1) refers to soaking at 25-40° C. for 0.5-1 h;
[0019] The reaction temperature of the self-assembly in step (1) is 25-40°C, and the reaction time is 12h-36h, preferably 24h at 35°C.
[0020] The nitrogen-containing organic compound in step (2) is at least one of dicyandiamide, melamine, etc., including but not limited to dicyandiamide, preferably dicyandiamide.
[0021] The amount of the nitrogen-containing organic compound in step (2) is 0.05-0.5 g / cm 2 , the figure of merit is 0.15g / cm 2, where area is the area of graphite felt.
[0022] The high temperature carbonization in step (2) refers to keeping the temperature at 600-900°C for 0.5h-3h; preferably keeping the temperature at 850°C for 0.5h-1h, with a nitrogen flow rate of 30-80ml / min.
[0023] The high temperature carbonization in step (2) is preferably N 2 High temperature carbonization under atmosphere.
[0024] A graphite felt / cobalt@nitrogen doped carbon nanotube array self-supporting fabric electrode prepared by the above method. That is, a simple strategy to in situ grow highly nitrogen-doped and oxygen-defect-rich carbon nanotubes encapsulated Co particles (GF / Co@NCNTs) on a graphite felt substrate as a flexible self-supporting bifunctional catalytic electrode for ZAB. In the process of the synthesis, a metal organic framework is in situ grown on an acid-treated modified graphite felt substrate by a simple room temperature self-assembly method to obtain a semi-encapsulated nanoparticle metal with uniform adsorption and multiple active sites. Using dicyandiamide (DCD) as a carbon source, an M-Nx-C type carbon nanotube (NCNTs) electrocatalyst is in situ grown on a three-dimensional flexible metal organic framework conductive substrate by chemical vapor deposition (CVD).
[0025] The graphite felt / cobalt@nitrogen doped carbon nanotube array self-supporting fabric electrode has an electrode loading of 1.8-3.0 mg / cm 2 .
[0026] The GF / Co@NCNTs synthesized in the present invention exhibit excellent trifunctional catalytic activity and outstanding stability. Its ORR, OER, HER and stability tests are not inferior to those of commercial Pt / C and RuO 2 . When used as a liquid ZAB air electrode, it can stably circulate for more than 350 hours. When used as a solid flat ZAB air electrode, a high open circuit voltage of 1.56V was achieved, which shows extremely excellent mechanical stability. Two FZABs in series can light up the LED light board and drive the car in a bent state. When three FZABs are connected in series, they can charge a smartphone, showing excellent output power and mechanical flexibility. In addition, the present invention integrates a flexible energy storage component with a flexible sensor component to obtain a wearable device with a self-powered sensor system, which can monitor human activities such as speaking, bending fingers, and pulse beating in actual situations. In addition, this type of electrocatalyst assembled flexible zinc-air battery is used as a power source for self-driven water electrolysis to produce hydrogen. The catalyst electrode is used as the cathode and anode to assemble a water electrolysis device, and the water drainage gas collection method is used to collect H on both sides of the H-type electrolyzer. 2 / O 2 .
[0027] The above-mentioned graphite felt / cobalt@nitrogen doped carbon nanotube array self-supporting fabric electrode is applied in zinc-air batteries, flexible wearable devices, pressure sensors, and self-driven water electrolysis to produce hydrogen, and is not limited to the application in zinc-air batteries.
[0028] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0029] (1) The nitrogen-doped carbon nanotube-coated cobalt metal alloy array structure fabric electrode prepared by the present invention is a self-supporting material. When preparing the electrode material, in order to avoid the use of binders and conductive agents and cover the reactive sites, in-situ growth of the material on a flexible substrate is the best solution. Due to the inherent advantage of close contact between the catalyst and the electrode, the self-supporting structure can be directly used as a ZAB electrode without the need for additional adhesives, thereby improving conductivity and catalytic performance. This method does not require binders and industrial ball milling coating methods, and can be directly self-grown on flexible materials, reducing industrial investment. The synthesis process is simple, highly repeatable, and can be quickly scaled up for industrialization.
[0030] (2) The present invention uses a graphite felt substrate that is inexpensive, has good adsorption, is lightweight, flexible, corrosion-resistant, has good resilience, and is highly conformal. It is mostly used in the field of vanadium redox flow batteries, but only rarely in the field of zinc-air batteries. It has strong and uniform adsorption of metal particles, reduces clusters during the generation of carbon nanotubes, and disperses high-density and well-defined metal particles on carbon nanotubes. The preparation method is universal and scalable, and can prepare a variety of bimetallic alloy carbon tube catalysts with excellent performance.
[0031] (3) The present invention develops a wearable device of a self-powered sensing system that integrates a flexible energy storage component with a flexible sensing component. The graphite felt substrate has certain compressibility and good mechanical properties, and is suitable for the coordinated application of flexible batteries and wearable sensors. Because of its different resistance outputs under different compression ratios, it is possible to monitor human activities such as speaking, finger bending, pulse beating, etc. in actual situations through this change, so as to expand the innovative application of zinc-air batteries.
[0032] (4) The fabric electrode prepared by the present invention also has excellent HER performance. The electrocatalyst is assembled into a flexible zinc-air battery as a power source for self-driven water electrolysis and hydrogen production. The catalyst electrode is used as the cathode and anode to assemble a water electrolysis device. In order to further explore the actual performance of the water electrolysis device, the water drainage gas collection method is used to collect H on both sides of the H-type electrolyzer. 2 / O 2 , further advancing the practical application of zinc-air batteries and demonstrating the great potential of this device in practical applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 Scanning electron microscope (SEM) images of the GF / Co@NCNTs fabric electrode prepared in Example 1 at different magnifications, including (a) blank GF; (b) GF / Co prepared in Example 1; (c)-(d) scanning electron microscope (SEM) images of GF / Co@NCNTs at different magnifications.
[0034] Figure 2 HR-TEM images and EDS mapping images of the GF / Co@NCNTs fabric electrode prepared in Example 1, where (a)-(c) represent HR-TEM images, and (d) represents an EDS mapping image.
[0035] Figure 3 These are actual pictures of the GF / Co@NCNTs fabric electrode prepared in Example 1 and the NF / Co@NCNTs electrode, CF / Co@NCNTs electrode, and CC / Co@NCNTs electrode prepared in Example 3.
[0036] Figure 4 LSV of OER, ORR, and HER of the GF / Co@NCNTs fabric electrode prepared in Example 1 and the CF / Co@NCNTs electrode and CC / Co@NCNTs electrode prepared in Example 3.
[0037] Figure 5 The GF / Co@NCNTs nitrogen-doped carbon nanotubes coated with metal Co flexible fabric electrodes prepared in Example 4 were assembled into a liquid zinc-air battery and subjected to a constant current test (current density of 10 mA cm -2 ) Cyclic performance diagram of charge and discharge test.
[0038] Figure 6 This is a performance diagram of the open circuit voltage test of a solid-state flexible zinc-air battery assembled with GF / Co@NCNTs nitrogen-doped carbon nanotubes coated with metal Co flexible fabric electrodes prepared in Example 5.
[0039] Figure 7 This is a diagram of the actual application of assembling a solid-state flexible zinc-air battery with the GF / Co@NCNTs nitrogen-doped carbon nanotube-coated metal Co flexible fabric electrode prepared in Example 5 to light up an LED light panel and charge a mobile phone.
[0040] Figure 8 A self-powered H-type electrolytic water splitting system was established based on the GF / Co@NCNTs|||GF / Co@NCNTs electrolyzer driven by a solid-state flexible zinc-air battery assembled with the GF / Co@NCNTs nitrogen-doped carbon nanotubes-coated metal Co flexible fabric electrodes prepared in Example 5.
[0041] Fig. 9 This is an application test diagram of a pressure sensor made of GF / Co@NCNTs nitrogen-doped carbon nanotubes coated with metal Co flexible fabric electrodes prepared in Example 1. DETAILED DESCRIPTION
[0042] The present invention is further described in detail below in conjunction with the examples and drawings, but the embodiments of the present invention are not limited thereto. If specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0043] The graphite felt pretreatment steps in the embodiment are as follows: cut the graphite felt into 5×2.5 cm 2 Small pieces. The cut graphite felt is placed in acetone for ultrasonic cleaning for 20 minutes to remove organic residues on the surface of the graphite felt, then the acetone is poured out, and anhydrous ethanol is added for ultrasonic cleaning for 20 minutes. During this period, fresh ethanol needs to be constantly replaced to wash away the residual acetone, and finally the graphite felt is placed in an oven to dry overnight. The dry carbon cloth is placed in a 100mL mixed solution of concentrated sulfuric acid, concentrated nitric acid and water, wherein 98% concentrated sulfuric acid (concentration of 18.4mol / L) and 98% concentrated nitric acid (concentration of 15.56mol / L) and water are mixed in a volume ratio of 1:1:1, the reaction temperature is 70°C, and the reaction time is 24h. In this way, the graphite felt is hydrophilized, and secondly, the surface of its carbon fiber is rougher, so that the surface area is increased and the particles are more fully adsorbed. Then take it out and wash it repeatedly with deionized water and anhydrous ethanol until it is neutral. Finally, dry it at 60°C and it can be used.
[0044] The electrochemical catalytic activities of the electrodes in the examples were evaluated using a typical three-electrode system, and all potentials mentioned were calibrated to the standard hydrogen potential (RHE).
[0045] If no temperature is clearly stated in the examples, it is assumed that the experiment was carried out at room temperature.
[0046] Example 1
[0047] This embodiment is a method for preparing a graphite felt / nitrogen-doped carbon nanotube-coated Co metal flexible fabric electrode material, named GF / Co@NCNTs, and the specific preparation steps are as follows:
[0048] (1) Preparation of GF / Co fabric electrode: 4 mmol Co(NO 3 ) 2 6H 2O and 0.8g PVP (polyvinyl pyrrolidone) (average molecular weight of 58000) were added to 100mL of methanol and marked as liquid A, which was pink. 40mmol 2-methylimidazole was added to 100mL of methanol and marked as liquid B, which was colorless. The pretreated graphite felt (5cm*2.5cm) was soaked in liquid A for 0.5h. After soaking in liquid A, liquid B was poured into liquid A and stirred quickly until it turned purple. The graphite felt was soaked in the mixed solution of A and B for 24h. The electrode was taken out and cleaned with methanol, and dried in an oven to obtain a GF / Co fabric electrode.
[0049] (2) Preparation of GF / Co@NCNTs: The GF / Co fabric electrode obtained above was placed flat on a porcelain boat containing 1.625 g of dicyandiamide, with the electrode covering the dicyandiamide. The porcelain boat was placed in the center of a tube furnace and then heated under N 2 At 5℃min -1 The temperature was raised to 850 °C and annealed for 1 hour at a heating rate of 40 mL / min. After the reaction was completed, the sample was naturally cooled to room temperature and the GF / Co@NCNTs fabric electrode was obtained. The electrode loading was about 2.5 mg / cm 2 .
[0050] Example 2
[0051] The present invention uses commercial Pt / C and RuO 2 Therefore, we also prepared Pt / C and RuO with the same loading amount as GF / Co@NCNTs fabric electrode as the ORR and OER benchmarks, respectively. 2 Catalyst graphite felt fabric electrode. And the same loading amount of Pt / C+RuO 2 Catalyst graphite felt fabric electrode as a benchmark for zinc-air batteries.
[0052] The specific preparation steps are as follows:
[0053] (1)RuO 2 Preparation of catalyst graphite felt fabric electrode: 2.5 mg of RuO 2 Add 100 μL Nafion (0.5 wt.%, wherein the solvent is anhydrous ethanol) and 900 μL anhydrous ethanol into a mixed solution, and then ultrasonically disperse for 1 hour to obtain a uniform black solution. Then, the uniformly dispersed black solution is drop-coated on both sides of the pretreated graphite felt substrate (the graphite felt is cut to an area of 1 cm*1 cm) to obtain RuO 2 Fabric electrodes.
[0054] (2) Preparation of Pt / C catalyst graphite felt fabric electrode: 2.5 mg of Pt / C was added to a mixture containing 100 μL of Nafion (0.5 wt.%, wherein the solvent was anhydrous ethanol) and 900 μL of anhydrous ethanol, and then ultrasonically dispersed for 1 hour to obtain a uniform black solution. The uniformly dispersed black solution was then drop-coated on both sides of the pretreated graphite felt substrate (the graphite felt was cut to an area of 1 cm*1 cm) to obtain a Pt / C fabric electrode.
[0055] (3)Pt / C+RuO 2 Preparation of catalyst graphite felt fabric electrode: 1.25 mg of Pt / C and 1.25 mg of RuO 2 Add 100 μL Nafion (0.5 wt.%, solvent: anhydrous ethanol) and 900 μL anhydrous ethanol into the mixture, and then ultrasonically disperse for 1 hour to obtain a uniform black solution. Then drop the uniformly dispersed black solution onto the two sides of the pretreated graphite felt zinc-air battery reaction area with an area of 1 cm 2 The reaction area is Pt / C+RuO 2 Fabric electrodes.
[0056] Example 3
[0057] For comparison, we followed the preparation method of Example 1, replaced the base graphite felt with different substrates: nickel foam, carbon cloth, carbon felt, and loaded the same catalyst to prepare NF / Co@NCNTs electrode, CF / Co@NCNTs electrode, and CC / Co@NCNTs electrode.
[0058] Example 4
[0059] The obtained GF / Co@NCNTs fabric electrode was used to assemble a zinc-air liquid battery. The GF / Co@NCNTs fabric electrode was used as a self-supporting (without binder and conductive additive) air cathode, the zinc sheet was used as the anode, and the electrolyte containing 0.2 mol L -1 Potassium hydroxide (concentration of 6 mol L) with zinc acetate additive -1 ) as the electrolyte to assemble into a liquid zinc-air battery.
[0060] Example 5
[0061] The obtained GF / Co@NCNTs or Pt / C+RuO 2 Fabric electrode assembly of zinc-air solid-state batteries, GF / Co@NCNTs, Pt / C+RuO 2 The fabric electrode was used as a self-supporting (without binder and conductive additive) air cathode, and the zinc sheet was used as the anode. -1 Potassium hydroxide (concentration of 11.25 mol L) as zinc oxide additive-1 ) 5 mL of electrolyte was mixed with 0.5 g of acrylic acid and 0.075 g of NN methylenebisacrylamide and stirred for 5 min, filtered into a culture dish, 75 μL of 0.3 M potassium persulfate was added as a traction agent, and the culture dish was slightly shaken to form a gel electrolyte.
[0062] Example 6
[0063] In order to expand the application of the present invention, the zinc-air solid-state battery assembled with the GF / Co@NCNTs fabric electrode of Example 5 was used as the power source for self-driven water electrolysis. The GF / Co@NCNTs fabric electrode was used as the cathode and anode to assemble the water electrolysis device. 1 mol / L KOH was used as the electrolyte. The water drainage gas collection method was used to collect H on both sides of the H-type electrolytic cell. 2 / O 2 .
[0064] Example 7
[0065] In order to expand the application of the present invention, a wearable device of a self-powered sensing system in which a flexible energy storage component and a flexible sensing component are integrated is assembled using the zinc-air solid-state battery assembled with the GF / Co@NCNTs fabric electrode of Example 5. Because of its different resistance outputs under different compression ratios, human activities such as speaking, finger bending, pulse beating, etc. can be monitored through this change in actual situations, so as to expand the innovative application of zinc-air batteries.
[0066] Figure 1 Scanning electron microscope (SEM) images of blank GF (a); GF / Co prepared in Example 1 (b); GF / Co@NCNTs (c)-(d) at different magnifications. The microstructure and morphology of the catalyst preparation process were compared by field emission scanning electron microscopy. Figure 1 Comparison between (a) and (b) shows that the metal Co particles are uniformly attached to the blank GF substrate. Figure 1 From (c) and (d), it can be seen that the carbon nanotubes grow uniformly on the GF substrate and grow upright outward, and the metal Co grows on the top of the carbon nanotubes.
[0067] Figure 2 In order to further characterize the detailed morphology of carbon nanotubes generated by the GF / Co@NCNTs nitrogen-doped carbon nanotubes coated with metal Co flexible fabric electrode prepared in Example 1, a transmission electron microscope (TEM) test diagram was conducted. Figure 2 From (a) and (b), we can see that the nitrogen-doped carbon nanotubes have a long bamboo-like structure, with a tube wall of about 10 to 100 nm; and the metal Co with a particle size of 10 to 30 nm is mostly distributed at the top of the nitrogen-doped carbon nanotubes. Figure 2The HR-TEM of (c) shows that the 0.177nm lattice spacing of the metal Co particles corresponds to the (200) plane of Co in XRD (JCPDsNo.15-0806), while the 0.35nm lattice spacing of the nitrogen-doped carbon nanotube wall coated with metal Co corresponds to the (002) lattice plane of graphitic carbon (JCPDs No.41-1487), indicating that the metal Co is coated on the top of the nitrogen-doped carbon nanotube. Figure 2 (d) is an elemental image, showing the distribution of C, N, O and Co. The uniform distribution of C and N elements proves that N is successfully doped in the carbon nanotubes. In addition, the Co signal can be clearly detected in the top area of the nitrogen-doped carbon nanotubes, further revealing that the metal Co is encapsulated in the doped carbon nanotube array. Finally, it is worth noting that in addition to the Co signal where the top metal Co is distributed, there are also detection signals of N atoms bound to the walls of the carbon nanotubes, which indicates that there may be the generation of active sites for MNCs, and the generation of such active sites is believed to be beneficial to improving the catalytic activity of the catalyst in the electrochemical process.
[0068] Figure 3 These are actual pictures of the GF / Co@NCNTs fabric electrode prepared in Example 1 and the NF / Co@NCNTs electrode, CF / Co@NCNTs electrode, and CC / Co@NCNTs electrode prepared in Example 3. Figure 3 (a) is GF / Co@NCNTs prepared with GF as the substrate. The fabric electrode has excellent flexibility and can be bent and twisted at will, and the fabric electrode itself is not damaged at all, indicating that graphite felt is a good substrate for flexible electrodes of zinc-air batteries. Figure 3 (b) is a sample NF / Co@NCNTs based on nickel foam (NF). Because its morphology changes greatly during high-temperature calcination, it cannot be used as an electrode material for electrochemical testing. Figure 3 (c) is a material CF / Co@NCNTs based on carbon felt (CF). Although it has certain electrochemical properties, it is easy to break after calcination and cannot be used as a flexible zinc-air battery electrode material. Figure 3 (d) CC-based electrode CC / Co@NCNTs has good flexibility. Although it can be bent and twisted at will, it does not have a certain thickness like graphite felt and cannot be well used for multifunctional applications.
[0069] Figure 4 The LSVs of OER, ORR, and HER of the GF / Co@NCNTs fabric electrode prepared in Example 1 and the CF / Co@NCNTs electrode and CC / Co@NCNTs electrode prepared in Example 3 are shown in Table 1. Figure 4(a) LSV curves of OER on different substrates show that GF / Co@NCNTs prepared in Experimental Example 1 of the present invention can provide a lower starting potential and a larger current density. When the overpotential of GF / Co@NCNTs is only 260 mV, it can reach 10 mA cm -2 The current density of CC / Co@NCNTs (290mV) and CC / Co@NCNTs (310mV) is comparable. Figure 4 (b) The LSV curves of ORR on different substrates show that GF / Co@NCNTs exhibits the best ORR activity, and has significantly higher half-wave potential and limiting current density compared to other substrates. Figure 4 (c) The GF / Co@NCNTs fabric electrode shows better HER activity and higher limiting current density than electrodes on other substrates, indicating that the graphite felt substrate can significantly reduce the overpotential and increase the current density, revealing its superior OER, ORR, and HER catalytic activity.
[0070] Figure 5 The GF / Co@NCNTs nitrogen-doped carbon nanotubes coated with metal Co flexible fabric electrodes prepared in Example 4 were assembled into a liquid zinc-air battery and subjected to a constant current test (current density of 10 mA cm -2 ) Cyclic performance diagram of charge and discharge test. At a current density of 10 mA cm -2 The cycling stability of liquid Zn-air batteries with GF / Co@NCNTs air cathode was evaluated in continuous discharge / charge cycles. Figure 5 As shown in the figure, the initial charge and discharge potentials are 1.78V and 1.05V, respectively, and the gap is 0.73V. It is worth noting that the charge and discharge test lasted for more than 350h (>1000 cycles), and the voltage difference (ΔE) remained at 1.02V, indicating that the GF / Co@NCNTs air cathode exhibits extremely excellent long-term durability. This shows that GF / Co@NCNTs can be used as the air cathode of zinc-air batteries to achieve excellent battery performance.
[0071] Figure 6 This is the performance diagram of the open circuit voltage test of the solid-state flexible zinc-air battery assembled with GF / Co@NCNTs nitrogen-doped carbon nanotubes coated with metal Co flexible fabric electrodes prepared in Example 5. Figure 6 It can be seen that GF / Co@NCNTs has a high open circuit voltage (1.56 V) higher than Pt / C+RuO 2 (1.45V), and is close to the theoretical open circuit voltage of 1.66V.
[0072] Figure 7This is a diagram showing the actual operation of assembling a solid-state flexible zinc-air battery with a metal Co flexible fabric electrode coated with GF / Co@NCNTs nitrogen-doped carbon nanotubes prepared in Example 5 to light up an LED light panel and charge a mobile phone. Figure 7 As shown, the solid-state flexible zinc-air battery (FZAB) assembled with GF / Co@NCNTs as air electrodes was used to light up the blue LED light board under different bending conditions by connecting two FZABs in series. The light board assembled with 40 commercial blue LED beads was successfully lit up from flat, single piece bent 90°, and two pieces bent 90°, and the brightness of the light board remained unchanged, proving that it has the potential to become a portable power source and has excellent mechanical properties.
[0073] Figure 8 Based on the GF / Co@NCNTs nitrogen-doped carbon nanotubes coated with metal Co flexible fabric electrodes prepared in Example 5, a solid-state flexible zinc-air battery driven electrolyzer based on GF / Co@NCNTs|GF / Co@NCNTs was assembled. Two GF / Co@NCNT fabric electrodes were placed vertically downward and parallel to each other. The two ends were respectively connected to the positive electrode and the negative electrode of the power supply device of the solid-state zinc-air battery in series assembled by the two GF / Co@NCNT fabric electrodes, and a self-powered H-type electrolytic water decomposition system was established. Figure 8 It can be seen that when FZABs are connected to the H-type electrolytic water splitting system, a large number of bubbles are generated on the surface of the GF / Co@NCNTs cathode and the GF / Co@NCNTs anode. In order to further explore the actual performance of the water electrolysis device, we collected and measured the H generated by the self-driven water splitting system. 2 and O 2 The volume of Figure 8 The right side records the H collected by the water drainage method within 0, 10, 20, 30, 40, and 50 minutes. 2 (above) and O 2 (below) volume, from Figure 8 The left figure shows that H 2 The precipitation rate was 0.98 mL min -1 ,O 2 The precipitation rate was 0.50 mL min -1 , electrolysis H 2 :O 2 The ratio is 1.96:1, which is close to the electrolytic H 2 :O 2 The theoretical ratio is 2:1, and the high hydrogen production efficiency of this self-driven water splitting system is comparable to that of some efficient ZABs-driven alkaline water electrolyzers.
[0074] Fig. 9This is an application test diagram of a pressure sensor made of GF / Co@NCNTs nitrogen-doped carbon nanotubes coated with metal Co flexible fabric electrodes prepared in Example 1. Fig. 9 (a) shows that when GF / Co@NCNTs is compressed by 60% by external force, it can recover to a state close to the original state, indicating that GF / Co@NCNTs has good resilience and recovery ability. In order to promote the application of the present invention, the GF / Co@NCNTs nitrogen-doped carbon nanotubes coated with metal Co flexible fabric electrodes prepared in Example 1 are used as solid-state flexible zinc-air batteries and wearable strain sensor-battery integrated devices. Fig. 9 It can be seen from the (b)-(e) output relative resistance change-time curves that it can detect (b) pulse beating; human body movement (c) forearm muscle relaxation and contraction movement; (d) finger joint bending and extension movement; because it has a certain sensitivity to strain, it further monitors the output signal of the resistance change of more subtle physiological signals (d) vocal vibration ("Wei" and "nihao") and (b) pulse beating; the signal can be detected because the vibration of the vocal cords is transmitted to the throat skin during speaking, thereby generating variable stress on the strain sensor-battery integrated device. The more subtle pulse beating signal can be detected because the pulse beating is transmitted to the skin, thereby generating variable pressure on the GF / Co@NCNTs pressure sensor-battery integrated device. Therefore, the pressure sensor-battery integrated device based on GF / Co@NCNTs of the present invention has broad application prospects in sports monitoring and medical monitoring systems.
[0075] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a graphite felt / cobalt@nitrogen-doped carbon nanotube array self-supporting fabric electrode, characterized in that The following steps are involved: (1) Preparation of GF / Co fabric electrode by room temperature self-assembly method: Soluble cobalt salt and polyvinyl pyrrolidone are added to methanol, marked as liquid A, and graphite felt is immersed in liquid A; dimethyl imidazole is added to methanol, marked as liquid B; after immersion in liquid A, liquid B is poured into liquid A and stirred until it turns purple, and then the graphite felt is immersed in the mixed solution of liquid A and liquid B and allowed to stand for self-assembly, and the graphite felt is taken out, cleaned, and dried to obtain a GF / Co fabric electrode; (2) Preparation of GF / Co@NCNTs fabric electrode by vapor deposition method: The fabric electrode obtained in the above step (1) is placed flat on a porcelain boat containing nitrogen-containing organic compounds, keeping the fabric electrode covering the nitrogen-containing organic compounds, and the porcelain boat is placed in the center of a tube furnace. Then, high-temperature carbonization is carried out under N2 or inert atmosphere. After the reaction is completed, it is naturally cooled to room temperature and the sample is taken out to obtain a GF / Co@NCNTs self-supporting fabric electrode.
2. The method for preparing the graphite felt / cobalt@nitrogen doped carbon nanotube array self-supporting fabric electrode according to claim 1, characterized in that: The graphite felt described in step (1) is first pretreated before the operation of step (1), and the pretreatment specifically includes the following steps: the graphite felt is ultrasonically cleaned in acetone to remove organic residues on the surface of the graphite felt, then the acetone is poured out, anhydrous ethanol is added to ultrasonically clean to remove residual acetone, and then dried, and then placed in an acidic solution to stir and react, and finally taken out and repeatedly washed with water and ethanol until neutral, and dried before being used in step (1).
3. The method for preparing the graphite felt / cobalt@nitrogen doped carbon nanotube array self-supporting fabric electrode according to claim 2, characterized in that: The acidic solution in the pretreatment is a mixed aqueous solution of sulfuric acid and nitric acid, the reaction temperature in the pretreatment is 60° C. to 100° C., and the reaction time is 12 to 36 hours.
4. The method for preparing the graphite felt / cobalt@nitrogen doped carbon nanotube array self-supporting fabric electrode according to claim 1, characterized in that: The soluble cobalt salt in step (1) includes but is not limited to at least one of nitrate, sulfate, and acetate; The molar ratio of the soluble cobalt salt, polyvinyl pyrrolidone and 2-methylimidazole in step (1) is 1:0.001-0.006:5-20; The methanol added in step (1) satisfies: the concentration of soluble cobalt salt in solution A after complete dissolution is 0.01-0.05 mol / L, the concentration of 2-methylimidazole in solution B is 0.2-0.6 mol / L; 2 Add the corresponding amount of graphite felt into 2-10mL of liquid A.
5. The method for preparing the graphite felt / cobalt@nitrogen doped carbon nanotube array self-supporting fabric electrode according to claim 1, characterized in that: The soaking in liquid A in step (1) refers to soaking at 25-40° C. for 0.5-1 h; The reaction temperature of the room temperature self-assembly in step (1) is 25-40° C., and the reaction time is 12 h-36 h.
6. The method for preparing the graphite felt / cobalt@nitrogen doped carbon nanotube array self-supporting fabric electrode according to claim 1, characterized in that: The nitrogen-containing organic compound in step (2) is at least one of dicyandiamide and melamine, preferably dicyandiamide.
7. The method for preparing the graphite felt / cobalt@nitrogen doped carbon nanotube array self-supporting fabric electrode according to claim 1, characterized in that: The amount of the nitrogen-containing organic compound in step (2) is 0.05-0.5 g / cm 2 , where area is the area of graphite felt.
8. The method for preparing the graphite felt / cobalt@nitrogen doped carbon nanotube array self-supporting fabric electrode according to claim 1, characterized in that: The high temperature carbonization described in step (2) refers to keeping the temperature at 600-900° C. for 0.5 h to 3 h.
9. A graphite felt / cobalt@nitrogen doped carbon nanotube array self-supporting fabric electrode prepared according to the method according to any one of claims 1 to 8.
10. Application of the graphite felt / cobalt@nitrogen doped carbon nanotube array self-supporting fabric electrode according to claim 9 in zinc-air batteries, flexible wearable devices, pressure sensors, and self-driven water electrolysis to produce hydrogen.
Citation Information
Cited By
Catalytic modified graphite felt electrode for vanadium battery and preparation method
CN120221679A